2005
DOI: 10.1002/ijc.21033
|View full text |Cite|
|
Sign up to set email alerts
|

P73 functionally replaces p53 in Adriamycin‐treated, p53‐deficient breast cancer cells

Abstract: p53-related genes, p73 and p63, encode 2 classes of proteins, TAp73/p63 and DN-p73/p63. TA-p73/p63 demonstrate p53-like properties including gene transactivation and cell death promotion, whereas DN-p73/p63 lack these p53-like functions. Although p53-deficient cancer cells are often less responsive to chemotherapy, they are not completely drug resistant, suggesting that other apoptotic pathways are at work. Here, we compared for the first time to our knowledge p73 and p63 activation in various breast cancer (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 31 publications
4
63
0
2
Order By: Relevance
“…72,73 Importantly, TAp73 can mediate apoptosis independent of functional p53 74,75 and can sensitize p53-deficient tumors to chemotherapy. [76][77][78][79] In line with these observations, we showed that the cytotoxic activity of various anticancer drugs, such as F-ara-A, was enhanced for CLL cells following CD40 ligation, particularly for CLL cells that lacked functional p53. Specific blocking of c-Abl tyrosine kinase, a kinase that stabilizes TAp73 by phosphorylation, 80,81 inhibited the capacity of CD40 ligation to induce high-level expression of TAp73 as well as Bid.…”
Section: Improving the Capacity Of Cll To Function As Effective Antigsupporting
confidence: 77%
“…72,73 Importantly, TAp73 can mediate apoptosis independent of functional p53 74,75 and can sensitize p53-deficient tumors to chemotherapy. [76][77][78][79] In line with these observations, we showed that the cytotoxic activity of various anticancer drugs, such as F-ara-A, was enhanced for CLL cells following CD40 ligation, particularly for CLL cells that lacked functional p53. Specific blocking of c-Abl tyrosine kinase, a kinase that stabilizes TAp73 by phosphorylation, 80,81 inhibited the capacity of CD40 ligation to induce high-level expression of TAp73 as well as Bid.…”
Section: Improving the Capacity Of Cll To Function As Effective Antigsupporting
confidence: 77%
“…Doxorubicin is a chemotherapeutic agent showing strong cytotoxic effect on T47D cell lines with IC 50 value of 15 nmol [11] . T47D cells could be resistant to doxorubicin due to p53 mutation [12,13] . Therefore, to prevent the tendency of resistence on T47D cells, combination of low concentration of doxorubicin with HIF is needed.…”
Section: Discussionmentioning
confidence: 99%
“…7). Doxorubicin inhibits cellular proliferation via p53-dependent and p53-independent mechanisms (43)(44)(45). In p53 wild-type MCF7 breast cancer cells, doxorubicin treatment causes an accumulation of p53 (45)(46)(47)(48), p53 recruits p21 (46) leading to decreased expression of cyclin B and cdc2 resulting in a cell cycle block at G 2 -M (47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…However, MDA-MB-436 cells express mutated p53 and it is unlikely that increases in p53 expression seen in these tumors are capable of recruiting p21 (49). In the absence of functional p53, p73 and p63 have been shown to replace p53 inducing p21 in doxorubicintreated breast cancer cells (44), and this is a possible mechanism by which p21 accumulates following sequential administration of doxorubicin and zoledronic acid. In addition to causing a cell cycle block at G 2 -M, experiments in colon cancer cells has shown that doxorubicin can also block G 1 by reducing expression of cyclin D1 (43).…”
Section: Discussionmentioning
confidence: 99%